The Influence Of Understanding Village Fund Accounting And Community Participation In Fund Management Village With The Principle Of Tri Pantangan As A Variable Moderation - Ayem, Sri; Anggita, Saskia (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
The purpose of this study was to determine the effect of accounting understanding and community participation on village fund management with the principle of tri pantang as a moderator variable in villages in Tumbangtiti District, Ketapang Regency. This research method uses primary data, and the data collection method uses a questionnaire technique. The population in this study includes all village officials in the Tumbangtiti District, Ketapang Regency, consisting of the Village Head, Village Secretary, Treasurer, and Finance Officer. The sampling technique used is non-probability obtained through questionnaire distribution, with a total of 64 respondents. The results of this study indicate that accounting understanding has a positive effect on village fund management, community participation has a positive effect on village fund management, tri pantang cannot moderate the effect of accounting understanding on village fund management, and tri pantang moderates the positive effect of community participation on village fund management.